Prevalence of and factors associated with adult-onset asthma in different ethnic groups: The HELIUS study. (April 2019) - Aarab, R.; Vijverberg, S.J.H.; Prins, M.; Snijder, M.B.; van Ree, R.; Fokkens, W.J.; Zwinderman, A.H.; Bel, E.H.D.; Maitland van der Zee, A.H.
Abstract: Little is known about adult-onset asthma in different ethnic groups. The aim of this study was to examine ethnic differences in the prevalence of adult-onset asthma and factors associated with this phenotype. Cross-sectional data of 23, 356 participants of the HELIUS study were used, including Dutch, South-Asian Surinamese, African Surinamese, Moroccan, Turkish and Ghanaian origin participants. Adult-onset asthma was defined as: self-reported asthma symptoms or start of asthma-medication at age ≥18 years combined with a smoking history <10 pack years. The prevalence of adult-onset asthma and its association with potential risk factors were assessed by logistic regression analyses. The adjusted prevalence of adult-onset asthma was higher in the Turkish, Moroccan and South-Asian Surinamese groups (4.9–6.0%) compared to the Dutch, Ghanaian and African Surinamese origin groups (2.4–2.6%). In addition to ethnicity, age, female sex, BMI, and doctors' diagnosis of nasal allergy/hay fever and chronic sinusitis/polyps were independently associated with adult-onset asthma. There are significant differences in the adjusted prevalence of adult-onset asthma among six ethnic groups. Highlights: The prevalence of adult-onset asthma varies significantly among six ethnic groups. Ethnic differences in prevalence persist after adjustment for known risk factors. Female sex, age, BMI and a doctors' diagnosis of nasal allergy/hay fever or sinusitis/polyps are independently associated with adult-onset asthma in all ethnic groups. Ethnic background is independently associated with the risk of adult-onset asthma.